Digital futures of heritage tourism: AI-driven economic models for sustainable development in Saudi Arabia (SDGs 8, 9, 11) - Ismail, Sayed M. (Research Journal in Advanced Humanities, 2025)
The global heritage tourism sector is increasingly turning to sophisticated digital technologies to address complex challenges in operational management, economic sustainability, and cultural preservation. This synthesis reviews recent scholarly contributions that demonstrate the transformative impact of these technologies. Studies employing predictive analytics, including machine learning and autoregressive integrated moving average (ARIMA) models, are proving effective in forecasting key economic metrics such as visitor expenditure, enabling more robust financial planning. Simultaneously, the integration of augmented reality (AR) and deep learning algorithms is being pioneered to create immersive and personalized visitor experiences, which in turn drives increased visitation and revenue generation. Furthermore, sentiment analysis and big data analytics offer powerful mechanisms for optimizing operational performance by systematically evaluating tourist feedback and streamlining logistical parameters. On the operational front, AI-driven tools are critical for enhancing safety and efficiency, particularly in managing large-scale events through improved crowd and traffic control systems. The adoption of Building Information Modeling (BIM) further contributes to operational sustainability by facilitating energy efficiency, reducing lifecycle costs, and improving collaboration among stakeholders in heritage conservation projects. Beyond economic and operational metrics, the digital transformation of heritage also fosters socio-cultural benefits. Participatory planning approaches and digital literacy programs empower local communities, enhance workforce readiness, and ensure that conservation efforts—such as the restoration of historical sites—reinforce cultural identity while generating local economic benefits. The confluence of artificial intelligence, digital transformation, and community-focused strategies creates a powerful framework for the sustainable management of cultural heritage. These integrated technological solutions not only optimize revenue streams and bolster operational resilience but also promote inclusive growth and community development. Consequently, this body of research underscores the significant role of technology in advancing the United Nations' Sustainable Development Goals (SDGs), particularly SDG 8 (decent work and economic growth), SDG 9 (industry, innovation, and infrastructure), and SDG 11 (sustainable cities and communities).